Prevalence of minimal hearing loss in South Korea. - Ji Eun Choi (PLoS ONE, 2017)
This study evaluated the prevalence of minimal hearing loss (MHL) in South Korea based on the 2010 to 2012 Korea National Health and Nutrition Examination Survey. A total of 16,630 representative individuals (older than 12 years) who completed ear examinations and structured questionnaires were analyzed. Only participants who had normal tympanic membranes were included. MHL was categorized into the following three groups: 1) unilateral sensorineural hearing loss (USHL, pure-tone average (PTA) ≥ 15 dB in the affected ear), 2) bilateral sensorineural hearing loss (BSHL, 15 dB ≤ PTA < 40 dB in both ears), and 3) high-frequency sensorineural hearing loss (HFSHL, two or more high-frequency thresholds > 25 dB in either ear). To evaluate clinical symptoms, subjective hearing status, tinnitus, and quality of life of each MHL group were compared to those of normal-hearing listeners. The use of hearing aids (HAs) was also investigated in the MHL population. The prevalence of normal hearing and MHL were 58.4% and 37.4%, respectively. In univariate analyses, the prevalence of MHL increased with age. It was significantly increased in males. Regarding clinical symptoms, 13.0% and 92.1% of participants with MHL reported difficulties with hearing and annoying tinnitus, respectively. In multivariate analyses, these proportions were significantly higher in the MHL groups than in normal-hearing listeners. Participants with MHL also showed significantly lower Euro Qol-5D index scores than did normal-hearing listeners. Regarding hearing rehabilitation, among minimally hearing impaired participants with subjective hearing loss, only 0.47% of individuals used HAs. Our results reveal that MHL is common in South Korea. It is associated with significant subjective hearing loss, tinnitus, and poor quality of life. Therefore, clinicians need to pay attention to this special group and provide proper counselling and rehabilitative management.